Does Health Insurance Affect the Completeness of Antenatal Care? - Wulandari, Ratna Dwi; Laksono, Agung Dwi (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2021)
The antenatal treatment has been ineffective in reducing maternal mortality. Therefore, this study aimed to examine health insurance effect on Indonesia's antenatal care quality. The 2017 Indonesian Demographic and Health Survey data were processed. Moreover, a sample size of 15,351 participants was selected using the analysis unit of study for women aged 15 to 49. In the final stage, Binary Logistic Regression was used, while other variables examined besides antenatal treatment included health insurance, residence, age, marital, education, parity, and wealth. Based on the complete category of antenatal care visits, women that did antenatal care visits were â‰¥ four, occupied by both types of health insurance ownership. The multivariable analysis indicated that health insurance ownership affects antenatal care completeness as insured women were 1.394 times higher than uninsured women (OR= 1.394; 95% CI= 1.257-1.546). Result showed other determinant variables, namely age, education, parity, and wealth were also found. In conclusion, health insurance gives Indonesian women a better possibility of receiving complete antenatal care.